(untitled) (Journal of Monno Medical College, 2023)
Background : Postoperative wound infection is a common consequence following laparotomy for peritonitis. Peptic ulcer perforation followed by peritonitis remains as an important cause of mortality. In severe peritonitis, the use of exploratory laparotomy and intra-operative lavage with large amount of saline solution has been the standard of care to reduce risk of postoperative infections. Objective: To compare the outcome between povidone iodine mixed normal saline (N/S) lavage and conventional normal saline lavage in the management of peritonitis in a tertiary care public hospital in Bangladesh. Methodology: This was a randomized clinical trial conducted in the department of Surgery, Shaheed Ziaur Rahman Medical College Hospital, Bogura during July 2013 to December 2013. There were total 50 patients, selected by purposive sampling as a diagnosed case of peritonitis due to peptic ulcer perforation. All the patients were divided into 2 groups by using coin toss as group A (conventional N/S) and group B (povidone iodine mixed with N/S). The data were collected using the pretested data collection sheet. Results were tested by chi-square test to see their level of significance with a p-value at <0.05. Results: The maximum (17, 34.0%) patients presented as peritonitis due to peptic ulcer perforation was from 18-30 years age group. The mean age of the patient was 29.16±9.25 years (age range: 18-61 years). The female to male ratio were 5.25:1 and 3.16:1 in group A and B respectively. Some (22, 44.0%) of the patients showed 13-18 hours delay since first symptom appeared. Fever (88.0% vs 80.0%), surgical site infection (SSI) (32.0% vs 24.0%), burst abdomen (20.0% vs 12.0%), intra-abdominal sepsis (8.0% vs 4.0%) were evident as postoperative complications in the groups A and B respectively. Only 1 (4.0%) patient died among group A patients due to sudden cardiac arrest. Mean hospital stay was a little lower among group B patients with milder complications and good outcome (though difference was not statistically significant). Conclusion: The outcome was observed better in case of using povidone iodine mixed with normal saline for peritoneal lavage. J Monno Med Coll June 2022;8(2): 36-39